1998
DOI: 10.1073/pnas.95.12.6953
|View full text |Cite
|
Sign up to set email alerts
|

Altered spectra of hypermutation in antibodies from mice deficient for the DNA mismatch repair protein PMS2

Abstract: Mutations are introduced into rearranged Ig variable genes at a frequency of 10 ؊2 mutations per base pair by an unknown mechanism. Assuming that DNA repair pathways generate or remove mutations, the frequency and pattern of mutation will be different in variable genes from mice defective in repair. Therefore, hypermutation was studied in mice deficient for either the DNA nucleotide excision repair gene Xpa or the mismatch repair gene Pms2. High levels of mutation were found in variable genes from XPA-deficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(85 citation statements)
references
References 41 publications
5
79
1
Order By: Relevance
“…Several studies have found reduced mutation rates in mismatch repair-deficient mice (11,14,16) and relative enhancement of mutations at the AGC/GCT hot spots (16) or at G and C bases (13,15). Rada et al (16) inferred from this observation that the mutator has two components, one that is dependent on the mismatch repair protein MSH-2 and another that is MSH-2 independent.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have found reduced mutation rates in mismatch repair-deficient mice (11,14,16) and relative enhancement of mutations at the AGC/GCT hot spots (16) or at G and C bases (13,15). Rada et al (16) inferred from this observation that the mutator has two components, one that is dependent on the mismatch repair protein MSH-2 and another that is MSH-2 independent.…”
Section: Discussionmentioning
confidence: 98%
“…There is considerable evidence that DNA MMR has an interplay with SHM (Cascalho et al 1998;Frey et al 1998;Jacobs et al 1998;Kim et al 1999;Kim & Storb 1998;Phung et al 1998;Rada et al 1998;Winter et al 1998). In our view, MMR is not involved in creating the mutations since in MMR-de¢cient mice the frequency of mutations and the mutation hot spots and cold spots are not signi¢-cantly altered (Kim et al 1999).…”
Section: A Model Of Somatic Hypermutation Revisitedmentioning
confidence: 99%
“…This pathway does not directly contribute to any of the V gene diversification mechanisms discussed above, since V-D-J joining, hypermutation, and class switch recombination were normal in animals deficient for repair factors XPA (Winter et al, 1998), XPB (Kim et al, 1997), XPC (Shen et al, 1997), XPD (Wagner et al, 1996), XPF (Tian et al, 2004a), XPG (Tian et al, 2004b), CSA (Kim et al, 1997), and CSB (Jacobs et al, 1998), with the exception of ERCC1 (Schrader et al, 2004). However, it was used as an experimental tool because the nucleotide excision repair capacity in a specific genomic region may reflect unusual aspects of the locus.…”
Section: Introductionmentioning
confidence: 99%